Fuzzy logic and model reference adaptive control of ship roll stabilization using fin actuator - Alarçin, E (TAYLOR & FRANCIS LTD, 2005)
A fuzzy-logic-based controller and a model reference adaptive control scheme are designed for ship roll stabilization. The simulated system was considered to be a one-degree-of-freedom (1-DOF) model. In order to achieve significant roll reduction are used fin actuator system. The effectiveness of this fuzzy control scheme is verified by comparison with model reference adaptive control simulation results. Simulation results show that the effectiveness of the fuzzy controller is better than model reference algorithm under the same conditions.
Keywords: Engineering; Oceanography